Norma dan Nilai dalam Ilmu Ekonomi Islam - Fahmi, Nurul (Tasamuh: Jurnal Studi Islam, 2019)
Islam has been set up with the norms and values in each discipline of knowledge. Including Islamic economics, Islamic economics as a social science and theology is not only derived from the Qur'an and as-Sunnah, but also stems from empirical phenomena and economic problems in the field. Epistemologically, Islamic economics is divided into two disciplines: First, normative Islamic economics, which is the study of Islamic sharia laws relating to property affairs and treasures. Second, positive Islamic economics, which is the study of Islamic concepts relating to property affairs and treasures, especially with regard to the production of goods and services. Norms and values created in Islamic economics aims to provide moral and ethical order in the economy itself, because it is basically the purpose of Islamic economics in the world is reaching the livelihoods and happiness in the Hereafter (hayatun thoyyibah and falah both in this world and in the hereafter)